2018
DOI: 10.3390/toxins10050200
|View full text |Cite
|
Sign up to set email alerts
|

High Production of LukMF’ in Staphylococcus aureus Field Strains Is Associated with Clinical Bovine Mastitis

Abstract: Staphylococcus aureus, a major cause of bovine mastitis, produces a wide range of immune-evasion molecules. The bi-component leukocidin LukMF’ is a potent killer of bovine neutrophils in vitro. Since the role of LukMF’ in development of bovine mastitis has not been studied in natural infections, we aimed to clarify whether presence of the lukM-lukF’ genes and production levels of LukMF’ are associated with clinical severity of the disease. Staphylococcus aureus was isolated from mastitis milk samples (38 clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 41 publications
3
44
0
Order By: Relevance
“…Intramammary challenge of cows with S. aureus strain S1444, which produces high levels of LukMF ′, resulted in more severe clinical signs than challenge with strains S1449 and S1463, which produce intermediate levels of LukMF ′, although SCC was similar between the groups (Vrieling et al, 2016). However, S1444 belongs to CC479 (Hoekstra et al, 2018), whereas the lineage to which S1449 and S1463 belong was not reported. Therefore, the strains may vary in more than just production of LukMF ′ and challenge of cows with strain S1444 lacking lukMF ′ would confirm the role of this toxin in virulence of bovine-adapted S. aureus.…”
Section: S Aureusmentioning
confidence: 95%
“…Intramammary challenge of cows with S. aureus strain S1444, which produces high levels of LukMF ′, resulted in more severe clinical signs than challenge with strains S1449 and S1463, which produce intermediate levels of LukMF ′, although SCC was similar between the groups (Vrieling et al, 2016). However, S1444 belongs to CC479 (Hoekstra et al, 2018), whereas the lineage to which S1449 and S1463 belong was not reported. Therefore, the strains may vary in more than just production of LukMF ′ and challenge of cows with strain S1444 lacking lukMF ′ would confirm the role of this toxin in virulence of bovine-adapted S. aureus.…”
Section: S Aureusmentioning
confidence: 95%
“…In addition, these regulatory systems also control expression and release of PAMPs, such as PSMs [38], and immune evasion factors that inhibit TLR-2 activation [12]. Since the CCs tested in this study belong to different agr types (CC133 to agr type I and CC151, CC479, CC425 to type II) [16,39] and CC479 S. aureus have been reported to carry a non-functional copy of the rot gene [23], differences in expression of these agr/rot controlled genes are likely and could be a possible explanation for the differential bMEC response towards ruminant-associated CCs. In addition, a previous study associated reduced bMEC activation by S. aureus with a negative Staphaurex latex agglutination test (SLAT) phenotype [29].…”
Section: Discussionmentioning
confidence: 98%
“…Although the level of bMEC activation by S. aureus likely contributes to the severity of an IMI, it is important to emphasize that the clinical severity of IMI depends on several factors, such host conditions and production of bacterial virulence factors [44]. Recently, we observed that S. aureus belonging to CC479 are associated with clinical rather than subclinical mastitis cases in cattle [23]. In the current study, CC479 isolates induced a stronger reaction from bMEC than the other bovine-associated lineage CC151, which could potentially contribute to the severity of mastitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jeannoel et al, [3] studied the synergistic effects of influenza virus and S. aureus in a monocytic cell-line model, and report that influenza virus potentiates the pro-inflammatory action of heat-killed S. aureus and contributes to the cytotoxicity of alpha-hemolysin on monocytes, but only few synergistic interactions were relevant in the ex vivo model. As regards the S. aureus infection in animals, Hoekstra et al, [4] report that production of the bi-component leucocidin LukMF' at higher levels is associated with clinical mastitis in cattle.…”
mentioning
confidence: 99%